Ethno-agronomic Management of Horticultural Inceptisols under Monoculture and Polyculture Using Nagari Local Ameliorant Resource Formulations - Herviyanti Herviyanti; An Nisa Mutiara Fathi; Irwan Darfis; M. Hafizh Ash Shiddiq; Defry Jonica Putri; Amsar Maulana; Ridho Ryswaldi (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Low soil surface charge and nutrient imbalances in Inceptisols threaten horticultural productivity in monoculture and polyculture systems. Ethno-agronomy management using local resources is expected to be a solution to these issues. The research aims to assess the effects of Nagari local ameliorant resource formulations (LARFs; bamboo biochar (BB), Tithonia green fertilizer (TGF), chicken manure (CM), and Agam compost (CA)) on surface charge and nutrients. A randomized complete block design (RCBD) was used to test 5 treatments: Control, LARF-I (BB + TGF + CM), LARF-II (BB + TGF + CA), conventional farming (CF), and Ministry of Agriculture Recommendations (MAR), with 3 replications, in Banuhampu, Agam. LARFs significantly improved soil surface charge properties (pH H2O, electrical conductivity (EC), percentage of organic matter (%OM), and cation exchange capacity (CEC)) and macronutrient levels (organic C (OC), total N, available P, and exchangeable K) compared with the control and conventional farming. LARF-I excelled in pH H2O, EC, %OM, and CEC under monoculture (+16–170%) and polyculture (+23–92%), outperforming CF by 11–157%. LARF-II led in OC (+91–112%) and total N (+37–441%), while LARF-I dominated available P (+122–328%) and exchangeable K (+60–78%). These enhancements increased crop nutrient uptake (N, P, and K) by up to 170% in string bean (monoculture) and broccoli (polyculture), with LARF-I achieving the highest overall increase. Yields increased most under LARF-II (string bean +33%, broccoli +74%, lettuce +70% compared to the control; 31–43% above CF), followed closely by LARF-I (+29–65% from the control; 21–29% above CF). These improvements enhanced soil fertility and nutrient availability, supporting better nutrient uptake and crop performance. LARFs promote sustainable restoration of soil fertility and support ethno-agronomic practices in horticulture.